The accuracy of the Quranic choice in Imam AL HASSAN AL MUJTABA speach"Pease be upon him" Descriptive analytical study (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study took upon itself an analysis of the Quranic texts that came in the folds of the words of Imam Al-Hassan Al-Mujtaba (peace be upon him)، in the light of the analysis of the speech. It included seven main axes followed by the Hassanic texts in which the Quranic verses were mentioned. The study is rich in Quranic values that are rich in the hadiths of the tribe (peace be upon him). أخذت هذه الدراسة على عاتقها تحليل النصوص القرآنيّة التي جاءت في ثنايا كلام الإمام الحسن المجتبى u، في ضوء تحليل الخطاب، وتضمنت سبعة محاور رئيسة، تتبعنا فيها النصوص الحَسَنيّة التي وردت فيها الآيات القرآنية، والتي عُدَّت شواهد للبحث في أمهات الكتب متفحصين ومدققين ومحللين، فكانت الدراسة غنية بالقيم القرآنية التي زخرت بها أحاديث الإمام الحسن u.